Conductivity and Transference Number Determination Protocols for Solid Oxide Cell Materials - Hardy, John S.; Kulkarni, Aniruddha P.; Stevenson, Jeffry W.; Marina, Olga A. (Frontiers in Energy Research, 2022)
To standardize materials and component characterization for next generation hydrogen production and energy generation solid oxide cell (SOC) technologies, test protocols are being established to facilitate comparison across the numerous laboratories and research institutions where SOC development is con-ducted. This paper proposes protocols for fundamental electrical properties characterization of SOC materials, including temperature- and pO2-dependent conductivity measurements, and use of the elec-tromotive force for determining the transference numbers, or contributions of each charge carrier (i.e., ions and electrons), to the total conductivity. The protocol for Archimedes density measurements is also provided as an integral technical to both of these methods.